Trabajo docente con padres y madres de familia, un recuento en la Educación Preescolar. México - Montaño Sánchez, Leticia (Universidad de Costa Rica, 2019)
This essay resents a historical overview of preschool education in Mexico. Particularly, it refers to the moments when the relationship of teachers with parents has been relevant for the organization and operation in kindergartens. This study also reviews the syllabi of preschool pre-service teacher education to confirm if the parent-teacher relations has been researched during this teacher training process. The analyses outlines major social and economic processes favoring the work of teachers with parents. It also discloses the presence of fathers and mothers in schools is due to their interest in providing their children with better conditions for their school work. A conclusion reached is that teacher’s work with fathers and mothers offers them experience which is scarcely gained during the practicum. Consequently, this article presents some recommendations to strengthen their pre-service teacher education.